2011
DOI: 10.1186/1471-2350-12-10
|View full text |Cite
|
Sign up to set email alerts
|

Testing the thrifty gene hypothesis: the Gly482Ser variant in PPARGC1Ais associated with BMI in Tongans

Abstract: BackgroundThe thrifty gene hypothesis posits that, in populations that experienced periods of feast and famine, natural selection favoured individuals carrying thrifty alleles that promote the storage of fat and energy. Polynesians likely experienced long periods of cold stress and starvation during their settlement of the Pacific and today have high rates of obesity and type 2 diabetes (T2DM), possibly due to past positive selection for thrifty alleles. Alternatively, T2DM risk alleles may simply have drifted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 51 publications
1
29
1
Order By: Relevance
“…The thrifty gene hypothesis has also been proposed as a plausible explanation for the increased body mass index observed in Polynesian populations. The findings suggest that certain genes remain a strong candidate thrifty gene in the Pacific (Myles et al, 2011). Although Neel's theory is significant to understanding of the evolutionary history of diabetes some recent study dispels the long held idea that indigenous people may have a specific gene that makes them more susceptible to diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…The thrifty gene hypothesis has also been proposed as a plausible explanation for the increased body mass index observed in Polynesian populations. The findings suggest that certain genes remain a strong candidate thrifty gene in the Pacific (Myles et al, 2011). Although Neel's theory is significant to understanding of the evolutionary history of diabetes some recent study dispels the long held idea that indigenous people may have a specific gene that makes them more susceptible to diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…A study lead by Myles et al (2011), suggested that the high frequency of the risk allele of the Gly482Ser variant in the PPARGC1A gene in Polynesians populations remains a thrifty allele in the Pacific populations. Another variant, the PC-1 Gln121, was also considered as a possible thrifty gene supported by studies in African and other groups (Rey et al 2012).…”
Section: Evolutionary Explanations For Obesitymentioning
confidence: 99%
“…By far the great majority of such early islanders subsisted -in large or at least critical partfrom nearshore marine foods, generally obtained from shallow water shoreflats, lagoons or reefs (Szabó and Amesbury, 2011;Wing and Wing, 2001). Yet the history of human occupation of islands, particularly in more remote settings, is often marked by times of plenty and times of less, variations that can be linked to climatic fluctuations and the antiquity of which may be marked by the 'thrifty gene' in island populations (Myles et al, 2011).…”
Section: Vulnerabilities Of Island Societiesmentioning
confidence: 99%